2020
DOI: 10.5380/psi.v24i1.64925
|View full text |Cite
|
Sign up to set email alerts
|

Bem-estar subjetivo em praticantes e não praticantes de meditação

Abstract: O Bem-Estar Subjetivo (BES) é composto por Afetos Positivos (AP), Negativos (AN) e Satisfação com a Vida (SV), que se referem aos componentes afetivos e cognitivos. As práticas meditativas, incorporadas às práticas integrativas aprovadas pelo SUS, são utilizadas para o relaxamento, incluindo alívio emocional e mental, e redução do estresse. Assim, este estudo procurou identificar relações entre os escores do BES e as práticas de meditação, frequência e anos de prática. Esta pesquisa foi composta por praticante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Different studies have demonstrated significant therapeutic effects of meditation practices for different groups or emotional demands (Barbosa et al, 2020;Carpena & Menezes, 2018;Carvalho & Votto, 2019;Guilherme & Pimenta, 2018;Moesgen et al, 2019). We highlight that Hernández and Martins (2020) assessed the subjective well-being of meditation practitioners. The authors conclude that people who frequently practice meditation have higher rates of what they called positive affects and life satisfaction.…”
Section: Stress Characterizes the Daily Life Of People Whose Family M...mentioning
confidence: 99%
“…Different studies have demonstrated significant therapeutic effects of meditation practices for different groups or emotional demands (Barbosa et al, 2020;Carpena & Menezes, 2018;Carvalho & Votto, 2019;Guilherme & Pimenta, 2018;Moesgen et al, 2019). We highlight that Hernández and Martins (2020) assessed the subjective well-being of meditation practitioners. The authors conclude that people who frequently practice meditation have higher rates of what they called positive affects and life satisfaction.…”
Section: Stress Characterizes the Daily Life Of People Whose Family M...mentioning
confidence: 99%
“…Estudos atuais evidenciam que adaptações técnicas de desenvolvimento da prática têm se mostrado eficazes no reconhecimento das emoções básicas e atuação sobre modos de agir no mundo de forma mais equilibrada e consciente, revisando as perspectivas e percepções das experiências, na redução da ansiedade, melhora na qualidade de vida, diminuição de sentimentos negativos e até mesmo aumentar a felicidade em geral (HERNÁNDEZ, MARTINS, 2020;WALLACE, 2017;ASSIS, PORTELLA, MALVA, 2016;CHAN et al, 2016).…”
Section: Introductionunclassified